Decision tree method for fault causes classification based on RMS-DWT analysis in 275 kV transmission lines network - Asman, Saidatul Habsah; Ab Aziz, Nur Fadilah; Ungku Amirulddin Al Amin, Ungku Anisa; Ab Kadir, Mohd Zainal Abidin (Multidisciplinary Digital Publishing Institute, 2021)
This paper presents a statistical algorithm for classification of fault causes on power transmission lines. The proposed algorithm is based upon the root mean square (RMS) current duration, voltage dip, and discrete wavelet transform (DWT) measured at the sending end of a line and the decision tree method, a commonly accessible measurable method. Fault duration of RMS current signal, voltage dip, and DWT gives concealed data of a fault signature as a contribution to decision tree calculation which is utilized to classify various fault causes. The proposed method was carried out in the MATLAB/SIMULINK programming platform based upon the information made with the fault analysis of the 275 kV sample transmission line considering wide variations in the operating conditions. The classifier performance of different parameters was also compared in a confusion matrix form to obtain the best classification results of the decision tree.